TERMINOLOGY AS A SPECIAL LINGUISTIC LAYER IN THE MODERN ARABIC LANGUAGE - Umarova, Nodirakhon I. (Oriental Journal of Philology, 2025)
Terminology, as a scientific discipline, is an important source of lexical enrichment for the Arabic language. The rapid development of science and technology has led to more than 90% of new words in modern languages being technical terms, highlighting the dynamic growth of specialized vocabulary. Despite the support of traditional linguistic academies, scientific and technological progress has resulted in the widespread borrowing of foreign terms. However, their adaptation has been accompanied by the emergence of synonymous designations, caused by the lack of standardized translation practices and terminological uncertainty.